Analysis of the Application Effect of PDCA Cycle Management Combined With Risk Factor Management Nursing for Reducing Infection Rate in Operating Room - Chen, Hong; Wang, Ping; Ji, Qi (Frontiers in Surgery, 2022)
Abstract Purpose: To explore the application effect of plan-do-check-action (PDCA) cycle management combined with risk factor management nursing in operating room. Methods: 150 surgical patients in our hospital from November 2020 to February 2021 were selected as the conventional group, and 150 surgical patients in our hospital from March 2021 to June 2021 were selected as the research group. Conventional group implemented routine infection management, research group implemented PDCA cycle management combined with risk factor management. The detection of pathogenic bacteria, incidence of incision infection, infection control, occurrence of irregular events and nursing quality in operating room were observed in the two groups. Results:The detection rates of Gram-negative bacillus and Gram-positive cocci, the infection rate of incision, the total incidence of irregular events in the research group were lower than those in the conventional group (P<0.05). The qualified rate of disinfection of object surface, hands of medical staff and air, the nursing quality scores in the research group were higher than those in the conventional group (P<0.05). Conclusion: PDCA cycle management combined with risk factor management nursing can reduce the detection rate of pathogenic bacteria and infection rate of incision in operating room, reduce the incidence of irregular events, improve the qualified rate of disinfection and greatly improve the quality of nursing, which can be considered to be widely used in clinical practice.